2010
DOI: 10.1002/pssb.200945510
|View full text |Cite
|
Sign up to set email alerts
|

Substrate dependent buffer‐layer assisted growth of nanoclusters

Abstract: The role of the substrate on the morphology of nanometer size clusters fabricated by buffer layer assisted growth (BLAG) was studied using scanning tunneling microscopy. Clusters of Fe and Co were deposited on Ag(111), Cu(100), Rh(111), and Pt(111) surfaces using identical BLAG parameters, which are temperature, as well as metal and buffer layer coverage. Semi‐hemispherical clusters are found on Ag(111) and Cu(100), while flat monolayer high islands are observed on Rh(111) and Pt(111) due to complete wetting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Recently, the intrinsic magnetic moment formation was studied on Rh clusters that were in direct contact with Ag(100) and Pt(997) substrates [283] and decoupled from the metal substrate by a thin Xe buffer layer [285]. A sketch of the experimental parameters is given in the inset of figure 19.…”
Section: Emergent Magnetismmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the intrinsic magnetic moment formation was studied on Rh clusters that were in direct contact with Ag(100) and Pt(997) substrates [283] and decoupled from the metal substrate by a thin Xe buffer layer [285]. A sketch of the experimental parameters is given in the inset of figure 19.…”
Section: Emergent Magnetismmentioning
confidence: 99%
“…(iii) Also alloying of the Rh with the substrate atoms cannot be excluded. Ab initio calculations actually predict the quenching of orbital and spin moments in alloyed nanostructures [285]. Future experiments must therefore exploit advanced synthesis methods with greater structural control, such as atomic manipulation, to study emergent magnetism in Rh or other nanostructures.…”
Section: Emergent Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Buffer layer assisted growth (BLAG), initially developed by Weaver and co-workers, is a novel method for growing nanoclusters onto nearly any substrate. , BLAG has been used to produce gold (Au), silver (Ag), and germanium (Ge) clusters, Au and palladium (Pd) bimetallic clusters, and II–VI quantum dots on various substrates. Although direct deposition of metal atoms spontaneously forms nanoclusters on many oxides and other stable surfaces through a Volmer–Weber growth mode, only certain combinations of metals and substrates can be used. The materials that do not work either have a high surface free energy that favors the formation of a dispersed film or they chemically react with the substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…We have already demonstrated that indeed, under these conditions, the morphology of the substrate underneath can be used as a template to tailor the cluster size and their lateral arrangement on the substrate. 7,8 In the present paper we investigate the mechanisms driving the dynamics during BLAG in detail, focusing on the early stage of cluster formation. The combined use of variable temperature scanning tunneling microscopy ͑VT-STM͒ and x-ray magnetic circular dichroism ͑XMCD͒ measurements allows us to monitor directly the growth mechanism of Co/Xe in case of absorption on two electronically very different metal substrates: Ag͑111͒ and Pt͑111͒.…”
Section: Introductionmentioning
confidence: 99%